Antidiarrhoeal activity of Aristolochia argentina Gris. (Aristolochiaceae) in rodents - Jésica D. Paredes, Ángela Sosa, María Fusco, Mauricio R. Teves, Graciela H. Wendel, Lilian E. Pelzer (Journal of Applied Pharmaceutical Science, 2016)
The roots of Aristolochia argentina are used in folk medicine for the treatment of colitis, diarrhoea and hemorrhoids. In this study, based on ethnobotanical lead, we evaluated the antidiarrhoeal activity of Aristolochia argentina lyophilized aqueous extract (AALE) in rats and mice using various models. The castor oil and magnesium sulphate induced diarrhoea, the small intestinal transit in mice and the intestinal fluid accumulation were used in this study. At the doses of 62.5, 125 and 250 mg/kg p.o., the AALE showed significant antidiarrhoeal activity in both models. The AALE significantly reduced the intestinal fluid accumulation in the castor oil induced enteropooling. AALE delays small intestinal transit possibly, at least in part, involving opioid and α2-adrenergic receptors. The phytochemical analysis revealed the presence of carbohydrates, flavonoids, tannins, saponins and anthraquinones. The results suggest that AALE showed antidiarrhoeal activity by inhibiting intestinal motility and enteropooling property, justify its use in traditional medicine.1
Keywords: Antidiarrhoeal, Aristolochia argentina, Aristolochiaceae, Intestinal transit, Intestinal fluid accumulation.